High-strength impact-resistant titanium alloy material and method of manufacturing the same

CN122918384APending Publication Date: 2026-10-16JIANGXI O-TA PRECISION TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510407697.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0007]首先,这些合金在强度和韧性之间的平衡存在挑战,特别是在高冲击、高强度和高韧性的应用场景中(如高尔夫球杆头的使用),往往无法在保证强度的同时,提供足够的延展性和韧性,容易导致材料的脆化或疲劳损坏

Benefits of technology

[0026]Beneficial Effects: The titanium alloy material developed in this invention can be applied to casting and sheet metal rolling, enabling the production of club heads of various shapes to meet different design requirements. Furthermore, the material's inherent heat resistance makes it suitable for high-temperature environments, maintaining its stability during both processing and final use. This durability ensures the long service life of golf clubs and allows them to perform excellently in various extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918384A_ABST
    Figure CN122918384A_ABST
Patent Text Reader

Abstract

The present application provides a high-strength impact-resistant titanium alloy material and a manufacturing method thereof, the manufacturing method comprising the following steps: providing a titanium alloy casting material, wherein the titanium alloy casting material comprises, based on the total weight of the titanium alloy casting material being 100 wt.%, 6.5-7.0 wt.% aluminum, 2.0-2.5 wt.% zirconium, 2.0-2.5 wt.% vanadium, 1.0-2.0 wt.% molybdenum, 0.5-1.5 wt.% iron, 0.1-0.3 wt.% boron, 0.15 wt.% or less silicon, 0.015 wt.% or less hydrogen, 0.15 wt.% or less oxygen, 0.05 wt.% or less nitrogen, 0.08 wt.% or less carbon, the balance being titanium, and inevitable impurities; subjecting the titanium alloy casting material to a forging step to form a titanium alloy forged plate blank; and subjecting the titanium alloy forged plate blank to a rolling step to form a titanium alloy forged plate material. The present application proposes a titanium alloy material with excellent performance, which realizes the excellent performance of high strength, high ductility and high durability at the same time through the synergistic effect of reasonable component ratio and added elements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a high-strength, impact-resistant titanium alloy material and its manufacturing method, particularly, but not exclusively, to a high-strength, impact-resistant titanium alloy material and its manufacturing method for use in aerospace, automotive industry, sporting goods and other fields. Background Technology

[0002] In recent years, with the popularization of golf and the improvement of its technical level, golf club heads, due to the nature of the sport, need to strike the hard golf ball at extremely high swing speeds. Furthermore, for performance reasons, the thickness of the striking face is typically between 2 and 4 millimeters. Therefore, the materials used in the clubhead often need to possess extremely high strength to withstand the harsh impact environment. Consequently, the research and development of golf club materials has become a focus of market attention. Clubhead materials need to possess excellent strength, toughness, and lightweight properties to cope with the high impact force during the swing and the wear and tear of long-term use. Therefore, choosing the right material is crucial for improving club performance.

[0003] Golf club heads were initially made with stainless steel as the base material. However, due to the lightweight and high strength properties of titanium alloy castings, titanium alloys (such as Ti-6Al-4V titanium alloy) have been actively developed in recent years to replace stainless steel.

[0004] For example, existing technology discloses a titanium-aluminum alloy for use in golf club heads, comprising 88 wt.% to 92 wt.% titanium and 7.5 wt.% to 10 wt.% aluminum. This titanium-aluminum alloy can be selectively supplemented with trace elements such as niobium, vanadium, molybdenum, chromium, iron, silicon, oxygen, and nitrogen to form a high-elongation material. This high-elongation material, when used in the body of the golf club head and combined with a 6Al-4V-Ti titanium alloy striking face with good rigidity, results in a golf club head product that offers excellent feel, shock absorption, and ball control, as well as adjustable clubhead angles, allowing for customization.

[0005] Furthermore, the applicant's previous Taiwan Application Publication No. 202100768A proposed a titanium alloy casting containing 6.5 to 8.5 wt.% aluminum, less than 2.5 wt.% zirconium, less than 2.0 wt.% molybdenum, less than 2.5 wt.% vanadium, 0.5 to 1.5 wt.% iron, 0.1 to 0.3 wt.% boron, less than 0.15 wt.% silicon, less than 0.015 wt.% hydrogen, less than 0.15 wt.% oxygen, less than 0.05 wt.% nitrogen, less than 0.08 wt.% carbon, a balanced amount of titanium, and unavoidable impurities.

[0006] However, while current titanium alloy materials have wide applications in some fields, they still face several technical challenges under certain high-performance requirements.

[0007] First, these alloys present a challenge in balancing strength and toughness, especially in high-impact, high-strength, and high-toughness applications (such as golf club heads). They often cannot provide sufficient ductility and toughness while ensuring strength, which can easily lead to embrittlement or fatigue damage of the material.

[0008] Secondly, existing titanium alloys do not perform ideally at high temperatures, especially during processing where their high-temperature resistance is weak, easily leading to a degradation of alloy properties. This poses a challenge for applications under high-temperature conditions (such as the manufacturing process of golf club heads). Existing materials may not maintain stable mechanical properties after heat forming or prolonged use.

[0009] Furthermore, traditional titanium alloys exhibit poor plasticity and machinability during processing, especially when manufacturing complex-shaped components. This increases the difficulty of material processing and demands higher precision in manufacturing techniques, thereby increasing costs and manufacturing complexity. Consequently, these alloys cannot be used in efficient production processes in actual manufacturing.

[0010] In addition, existing titanium alloy materials are also insufficient in terms of corrosion resistance and fatigue resistance, especially in extreme environments (such as high temperature, high pressure or repeated impact loads), where the material performance is prone to deterioration, which will affect the service life and stability of the final product.

[0011] Finally, although elements such as aluminum, zirconium, vanadium, and molybdenum have played a positive role in improving the properties of titanium alloys, current alloy composition design has not achieved an optimal balance of elemental proportions. When the aluminum content is too high, the alloy becomes more brittle, which in turn affects its ductility and durability; when the aluminum content is too low, the alloy's strength decreases, resulting in a shorter service life and failing to meet the requirements of high-strength applications.

[0012] Furthermore, it is extremely difficult for titanium alloys to surpass the physical properties of existing materials in both strength and elongation.

[0013] Therefore, it is necessary to provide a high-strength, impact-resistant titanium alloy material and its manufacturing method to solve the problems existing in the prior art. Summary of the Invention

[0014] To meet these needs, this invention extends the applicant's previous Taiwan Patent Application Publication No. 202100768A by developing a novel titanium alloy material. Based on the actual application conditions of golf products, the element ratios are more precisely adjusted, resulting in material with not only excellent mechanical properties but also good heat resistance. Whether cast or rolled, the material exhibits superior quality. Compared to the common Ti-6Al-4V alloy, the material of this invention surpasses it in strength and toughness, and its mechanical properties are not significantly affected even during machining or thermoforming, thus broadening its application range.

[0015] The main objective of this invention is to provide a high-strength, impact-resistant titanium alloy material and its manufacturing method, applicable to casting and sheet metal rolling, capable of producing clubheads of various shapes to meet different design requirements. Furthermore, the material's inherent heat resistance makes it suitable for high-temperature environments, maintaining its stability during both processing and final use. This durability ensures the long service life of golf clubs and allows them to perform exceptionally well in various extreme environments.

[0016] In view of this, the present invention provides a high-strength, impact-resistant titanium alloy material and a method for manufacturing the same. The manufacturing method includes the following steps: providing a titanium alloy casting material, wherein, based on a total weight of 100 wt.% of the titanium alloy casting material, the titanium alloy casting material comprises: 6.5 to 7.0 wt.% aluminum, 2.0 to 2.5 wt.% zirconium, 2.0 to 2.5 wt.% vanadium, 1.0 to 2.0 wt.% molybdenum, 0.5 to 1.5 wt.% iron, and 0.1 to 0.5 wt.% iron. The titanium alloy casting material contains 0.3 wt.% boron, less than 0.15 wt.% silicon, less than 0.015 wt.% hydrogen, less than 0.15 wt.% oxygen, less than 0.05 wt.% nitrogen, less than 0.08 wt.% carbon, a balanced amount of titanium, and unavoidable impurities; the titanium alloy casting material is subjected to a forging step to form a titanium alloy forged slab, wherein the forging step includes: a first heat forging step, wherein the heating temperature of the first heat forging step is 1100±20℃. The process includes: a second forging step, wherein the heating temperature of the second forging step is 950±10℃; a third forging step, wherein the heating temperature of the third forging step is 990±10℃; a fourth forging step, wherein the heating temperature of the fourth forging step is 850±10℃; a fifth forging step, wherein the heating temperature of the fifth forging step is 820±40℃; and a rolling step is performed on the titanium alloy forged slab to form a titanium alloy. Alloy forged sheet metal, wherein the rolling step includes: a first rolling step, wherein the heating temperature of the first rolling step is 900 to 1100°C; a second rolling step, wherein the heating temperature of the second rolling step is 700 to 800°C; a third rolling step, wherein the heating temperature of the third rolling step is 900 to 1100°C; and a fourth rolling step, wherein the heating temperature of the fourth rolling step is 700 to 800°C.

[0017] In some embodiments of the present invention, after the first forging step heats the titanium alloy casting material to 1100±20°C, the titanium alloy casting material is subjected to an upsetting and drawing step, and after forging, it is air-cooled to room temperature and the surface cracks are removed by grinding.

[0018] In some embodiments of the present invention, after the second forging step heats the titanium alloy casting material to 950±10°C, the titanium alloy casting material is subjected to an upsetting and drawing process, and after forging, it is air-cooled to room temperature and the surface cracks are removed by grinding.

[0019] In some embodiments of the present invention, the third forging step involves heating the titanium alloy casting material to 990±10°C, followed by an upsetting and drawing process, and then air cooling to room temperature and grinding to remove surface cracks.

[0020] In some embodiments of the present invention, the fourth forging step involves heating the titanium alloy casting material to 850±10°C, performing an upsetting and drawing process on the titanium alloy casting material, and then reheating it in the furnace after forging.

[0021] In some embodiments of the present invention, the fifth forging step involves heating the titanium alloy casting material to 820±40°C, and then alternately performing unidirectional pressing and circumferential shaping operations on the titanium alloy casting material to form the titanium alloy forging slab.

[0022] In some embodiments of the present invention, the rolling rate of the first and second rolling steps is 30% to 50%.

[0023] In some embodiments of the present invention, the third hot rolling step includes heating the titanium alloy forged slab to 900 to 1100°C and then hot rolling it, controlling the holding time to be 20 to 60 minutes, and then performing a water quenching step after the third hot rolling step.

[0024] In some embodiments of the present invention, the fourth rolling step includes heating the titanium alloy forged slab after the water quenching step in the third rolling step to 700 to 800°C and performing reversing rolling, wherein the fourth rolling step is rolled to 70% to 80% of the target plate thickness.

[0025] Furthermore, the present invention also provides a titanium alloy material manufactured by the manufacturing method described above, wherein, based on a total weight of 100 wt.% of the titanium alloy material, the titanium alloy material comprises: 6.5 to 7.0 wt.% aluminum, 2.0 to 2.5 wt.% zirconium, 2.0 to 2.5 wt.% vanadium, 1.0 to 2.0 wt.% molybdenum, 0.5 to 1.5 wt.% iron, 0.1 to 0.3 wt.% boron, less than 0.15 wt.% silicon, 0 The titanium alloy contains less than 0.015 wt.% hydrogen, less than 0.15 wt.% oxygen, less than 0.05 wt.% nitrogen, less than 0.08 wt.% carbon, a balanced amount of titanium, and unavoidable impurities, wherein the titanium alloy material has a tensile strength between 139 and 160 kSI, a yield strength between 139 and 150 kSI, an elongation between 12 and 16%, a hardness between 35 and 36 HRC, and a durability test firing count between 4000 and 6000 rounds.

[0026] Beneficial Effects: The titanium alloy material developed in this invention can be applied to casting and sheet metal rolling, enabling the production of club heads of various shapes to meet different design requirements. Furthermore, the material's inherent heat resistance makes it suitable for high-temperature environments, maintaining its stability during both processing and final use. This durability ensures the long service life of golf clubs and allows them to perform excellently in various extreme environments.

[0027] Furthermore, the titanium alloy material of this invention possesses excellent plasticity and machinability, making the manufacturing process of the clubhead more efficient, reducing manufacturing costs and improving production efficiency. Simultaneously, because the material maintains stability at high temperatures, it means that it retains consistent performance after multiple processing steps, thus meeting various design requirements.

[0028] Furthermore, the titanium alloy material of the present invention can surpass the physical properties of existing titanium alloy materials in both strength and elongation.

[0029] In summary, the titanium alloy material of this invention not only meets the current market requirements for high-strength, high-toughness clubheads and high ductility, but also possesses lightweight properties and good durability, providing a superior solution for golf. With the continuous increase in market demand, the titanium alloy material of this invention will show broad application prospects in golf and other high-performance application fields. Attached Figure Description

[0030] Figure 1 This is a schematic flowchart illustrating a method for manufacturing a high-strength, impact-resistant titanium alloy material according to an embodiment of the present invention.

[0031] Figures 2a to 2c A schematic diagram of the metallographic structure according to an embodiment of the present invention is shown; wherein Figure 2a This is a schematic diagram of metallographic structure magnified 1000 times using an optical microscope (OM); Figure 2b This is a schematic diagram of metallographic structure magnified 1000 times using a scanning electron microscope (SEM); Figure 2c This is a schematic diagram of the metallographic structure magnified 3000 times using a scanning electron microscope (SEM). Detailed Implementation

[0032] The term "tensile strength" as used herein refers to the maximum tensile force a material can withstand during stretching until it breaks or fractures. Tensile strength reflects a material's ability to resist tensile deformation and is commonly used as an indicator of a material's strength properties. The test method involves mounting a cylindrical or rectangular sample on a tensile testing machine and stretching it at a fixed speed until it breaks. The maximum load before fracture is measured as the tensile strength. Detailed test methods can be found in ASTM E8 / E8M standards, and tensile testing is performed using a Shimadzu universal testing machine.

[0033] The term "yield strength" as used in this article refers to the stress value at which a material, under tensile stress, transitions from elastic deformation to plastic deformation; that is, the stress at which the material begins to undergo permanent deformation and cannot fully recover. The test method is a tensile test, in which a gradually increasing load is applied to the material until the material exhibits significant plastic deformation, and the stress value at this point is recorded as the yield strength. Detailed test methods can be found in ASTM E8 / E8M standards, and tensile tests are performed using a Shimadzu universal testing machine.

[0034] The term "elongation" as used in this article refers to the ratio of the maximum elongation a material can withstand before fracture to its original measured length in a tensile test, usually expressed as a percentage. Elongation reflects the plasticity of a material, indicating the extent to which it can stretch under tension. The test method is a tensile test, in which the maximum elongation of the material from its original length to fracture or permanent deformation under applied tensile stress is measured, and the ratio to the original length is calculated. Detailed test methods can be found in ASTM E8 / E8M standards, and tensile tests are performed using a Shimadzu universal testing machine.

[0035] The term "Hardness HRC" as used in this article refers to the hardness value obtained by measuring the surface of a material using a diamond cone under a specified load, according to the Rockwell hardness test method. Specifically, HRC measures the hardness of metallic materials (such as steel) using a Rockwell Type C hardness scale. The hardness is determined by applying a specific load and measuring the depth of the indentation on the material surface. The test method involves using a 120-degree angled diamond cone and applying a load of approximately 150 kg. Detailed test methods can be found in ASTM E18 standard.

[0036] The terms "clubhead durability test" or "impact test" used in this article refer to high-energy impact testing of materials to simulate impacts or shocks that may be encountered in actual use, and to evaluate the durability and failure characteristics of materials under impact forces. The test method involves impacting the material surface with a steel ball or other spherical object at a certain speed and angle, and observing the damage to the material surface or structure to record cracking, deformation, or other damage phenomena.

[0037] To make the above-mentioned objectives, features and characteristics of the present invention more apparent and understandable, the relevant embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0038] Figure 1This is a schematic flowchart illustrating a method for manufacturing a high-strength, impact-resistant titanium alloy material according to an embodiment of the present invention. The manufacturing method includes the following steps: providing a titanium alloy casting material, wherein, based on a total weight of 100 wt.% of the titanium alloy casting material, the titanium alloy casting material comprises: 6.5 to 7.0 wt.% aluminum, 2.0 to 2.5 wt.% zirconium, 2.0 to 2.5 wt.% vanadium, 1.0 to 2.0 wt.% molybdenum, 0.5 to 1.5 wt.% iron, 0.1 to 0.3 wt.% boron, less than 0.15 wt.% silicon (e.g., greater than 0 wt.% and less than 0.15 wt.%), and 0.015 wt.%... The titanium alloy casting material contains less than 0.15 wt.% hydrogen (e.g., greater than 0 wt.% and less than 0.015 wt.%), less than 0.15 wt.% oxygen (e.g., greater than 0 wt.% and less than 0.15 wt.%), less than 0.05 wt.% nitrogen (e.g., greater than 0 wt.% and less than 0.05 wt.%), less than 0.08 wt.% carbon (e.g., greater than 0 wt.% and less than 0.08 wt.%), a balanced amount of titanium, and unavoidable impurities; the titanium alloy casting material is subjected to a forging step to form a titanium alloy forged slab, wherein the forging... The forging process includes: a first forging step, wherein the heating temperature of the first forging step is 1100±20℃; a second forging step, wherein the heating temperature of the second forging step is 950±10℃; a third forging step, wherein the heating temperature of the third forging step is 990±10℃; a fourth forging step, wherein the heating temperature of the fourth forging step is 850±10℃; and a fifth forging step, wherein the heating temperature of the fifth forging step is 820±40℃; and the forging is then... A titanium alloy forged slab is subjected to a rolling step to form a titanium alloy forged sheet, wherein the rolling step includes: a first rolling step, wherein the heating temperature of the first rolling step is 900 to 1100°C; a second rolling step, wherein the heating temperature of the second rolling step is 700 to 800°C; a third rolling step, wherein the heating temperature of the third rolling step is 900 to 1100°C; and a fourth rolling step, wherein the heating temperature of the fourth rolling step is 700 to 800°C.

[0039] The titanium alloy material of the present invention is based on aluminum, zirconium, vanadium and molybdenum, and its properties are enhanced by adding iron and boron. The combination of these components results in a significant improvement in the mechanical properties of the material.

[0040] In this invention, aluminum (Al) is the main element in the titanium alloy material, working synergistically with zirconium (Zr) to improve the alloy's strength and corrosion resistance. The addition of aluminum not only increases strength but also significantly reduces the alloy's density, giving it excellent specific strength, making it suitable for lightweight design applications. Zirconium in this alloy refines the grain size, further enhancing the material's strength while maintaining good ductility. Furthermore, zirconium effectively improves the titanium alloy's creep resistance in high-temperature environments and enhances its corrosion resistance, ensuring stability under high temperature and high pressure conditions.

[0041] Vanadium (V) and molybdenum (Mo) further stabilize the β-phase structure of titanium alloys and provide additional strengthening effects. The addition of vanadium not only improves the alloy's ductility and plasticity but also enhances its impact resistance under high dynamic loads. Molybdenum, as an effective solid solution strengthening element, significantly improves the alloy's high-temperature strength and creep resistance, while also enhancing its weldability, preventing cracks during welding, and improving the ease of manufacturing and repair.

[0042] The addition of boron (B) not only promotes the formation of the titanium boron (TiB) phase, significantly improving the strength and hardness of the material, enhancing its wear resistance, and reducing processing defects, but also effectively inhibits grain growth in titanium alloys at high temperatures, which is crucial for maintaining the material's mechanical properties. Especially under high-temperature processing conditions, a fine and uniform grain structure contributes to the material's ductility and creep resistance. Furthermore, trace amounts of iron (Fe) refine the grains, improving the material's plasticity and machinability, making titanium alloys more suitable for forming complex shapes.

[0043] The synergistic effect of these elements enables the titanium alloy to achieve a good balance in terms of strength, ductility, high temperature resistance, corrosion resistance and machinability, making it particularly suitable for industrial applications that require lightweight, high strength and high durability.

[0044] In actual testing, the material of this invention exhibits superior casting strength compared to existing titanium alloys Ti-6Al-4V (as shown in Table 1). The addition of trace amounts of boron (B) and iron (Fe) further enhances the overall performance of the titanium alloy. The presence of boron (B) stabilizes the titanium-boron (TiB) phase distribution in the alloy, improving the material's hardness and wear resistance. The addition of iron (Fe), through grain refinement, significantly improves the material's ductility and also enhances its machinability, making it suitable for various complex processes. Therefore, this titanium alloy not only possesses high strength and good ductility but also demonstrates excellent corrosion resistance and machinability, making it suitable for various demanding applications such as aerospace, automotive, and sporting goods. Table 1. Comparison of physical properties of casting materials

[0045] The titanium alloy material of this invention is not only excellent in casting, but also, due to its plasticity and thermal stability, when used in sheet metal fabrication through a specially customized process and heat treatment, exhibits more stable and superior physical properties compared to existing titanium alloy Ti-6Al-4V sheets (as shown in Table 2), making it particularly suitable for golf club head manufacturing. Golf club heads are subjected to extremely high impact forces during use, thus placing high demands on the material's strength, ductility, and fatigue resistance. By applying the aforementioned titanium alloy to the club head's striking face, ideal mechanical properties can be achieved, with a tensile strength between 139 and 160 kJ / s and an elongation between 12 and 16%. This effectively resists deformation under high impact, reduces material weight, and provides design flexibility. These superior properties allow the club head to maintain stability and durability while possessing higher rebound force and impact performance. It should be noted that the physical properties of this invention are significantly improved compared to those of the applicant's previous Taiwan Patent Application Publication No. 202100768A, overcoming the difficulty of simultaneously surpassing both strength and elongation.

[0046] Table 2. Comparison of physical properties between the titanium alloy sheet of the present invention and the Ti-6Al-4V alloy sheet of the prior art.

[0047] In terms of heat treatment, the titanium alloy material of the present invention has excellent heat resistance, and its mechanical properties are not significantly affected even during machining and heated molding. When the titanium alloy sheet of the present invention is heated in the temperature range of 500°C to 800°C, the difference in its mechanical properties compared with the original sheet does not exceed 6% (as shown in Table 3), ensuring the stability of the material under various processing and operating conditions. Table 3. Comparison of heat-treated physical properties of the titanium alloy sheet of the present invention

[0048] Furthermore, this invention further develops upon the extended materials disclosed in the applicant's previous Taiwan application No. 202100768A, and through data accumulation, finds more precise optimal proportions for individual components. Specifically, it limits the content of Al, Zr, and V elements. Taking the data from Examples 2 and 3 as shown in Tables 4 and 5 as examples, when the Al content is between 6.5 and 7 wt.%, the physical properties are most suitable for golf hitting surfaces requiring high strength and high ductility, and the measured clubhead durability limit is optimal. When the Al content continues to increase, it easily increases the brittleness of the board, reducing the ductility and durability stability of the material. This will make the durability quality of products made from the material unstable. Conversely, when the Al content continues to decrease, it leads to a decrease in strength, directly affecting the product's lifespan. In addition, to facilitate the testing of the durability limit, the clubhead durability test of this invention uses a thinner hitting surface thickness than commercially available materials (3.2 mm thick area / 2.6 mm thin area), and continuously fires golf balls at a fixed ball speed to hit the hitting surface to test the durability strength. Table 4. Test table for Al content adjustment in this invention. serial number Al Zr V Mo Fe B Example 1 5.38 2.11 2.34 1.25 1.42 0.17 Example 2 6.53 2.15 2.28 1.53 0.72 0.25 Example 3 6.87 2.36 2.14 1.54 1.05 0.22 Example 4 8.25 2.22 2.35 1.78 1.02 0.15 Table 5. Property Table of Al Content Adjustment Test Reference Material of the Invention

[0049] After determining the optimal Al content, a fixed Al content of 6.5 to 7 wt.% was used, and other components were fine-tuned for comparison. As shown in Tables 6 and 7, it can be determined that when the Zr and V content is between 2.0 and 2.5 wt.%, the physical properties suitable for use in golf club heads will be better. Adding components below these levels can easily lead to insufficient strength, which will also affect the strength and lifespan of the product. While excessive addition can further improve the strength of the material, the reduction in elongation will make the durability and stability of the product worse, which is not conducive to the use of golf products. Table 6. Test Table for Adjustment of Ingredients in this Invention serial number Al Zr V Mo Fe B Example 2 6.53 2.15 2.28 1.53 0.72 0.25 Example 3 6.87 2.36 2.14 1.54 1.05 0.22 Example 5 6.93 1.53 1.42 1.66 1.15 0.15 Example 6 6.55 2.33 1.21 1.53 1.12 0.15 Example 7 6.78 1.41 2.40 1.24 0.92 0.19 Example 8 7.05 3.22 2.88 1.37 0.88 0.23 Table 7. Property Table of Comparative Tests for Component Adjustment of the Invention

[0050] Based on the above test results, the inventors designed the composition of the titanium alloy ingot as shown in Table 8. Based on a total weight of 100 wt.% of the titanium alloy material, the titanium alloy material includes: 6.5 to 7.0 wt.% aluminum, 2.0 to 2.5 wt.% zirconium, 2.0 to 2.5 wt.% vanadium, 1.0 to 2.0 wt.% molybdenum, 0.5 to 1.5 wt.% iron, 0.1 to 0.3 wt.% boron, less than 0.15 wt.% silicon, less than 0.015 wt.% hydrogen, less than 0.15 wt.% oxygen, less than 0.05 wt.% nitrogen, less than 0.08 wt.% carbon, a balanced amount of titanium, and unavoidable impurities. Table 8. Ingot Composition Design of the Invention

[0051] The advantage of this invention lies in the synergistic effect of its composition design and added elements. By precisely controlling the proportions of aluminum, zirconium, and vanadium, and rationally adding trace amounts of boron, molybdenum, and iron, the material achieves an optimal balance of strength, hardness, ductility, and corrosion resistance. Furthermore, the material retains excellent plasticity and machinability during processing, making it suitable for large-scale production and application. These performance characteristics make this titanium alloy a promising high-performance material for aerospace, automotive, and sporting goods industries.

[0052] Example of titanium alloy material manufacturing process of this invention:

[0053] The titanium alloy preparation process of the present invention includes the following steps:

[0054] 1. Ingot casting process

[0055] The raw material configuration includes sponge titanium, aluminum briquettes, aluminum-zirconium alloy, aluminum-molybdenum alloy, aluminum-vanadium alloy, aluminum-iron alloy, and aluminum-boron alloy. Its composition includes the following components: 6.5 to 7.0 wt.% aluminum, 2.0 to 2.5 wt.% zirconium, 2.0 to 2.5 wt.% vanadium, 1.0 to 2.0 wt.% molybdenum, 0.5 to 1.5 wt.% iron, 0.1 to 0.3 wt.% boron, greater than 0 and less than 0.15 wt.% silicon, greater than 0 and less than 0.015 wt.% hydrogen, greater than 0 and less than 0.15 wt.% oxygen, greater than 0 and less than 0.05 wt.% nitrogen, greater than 0 and less than 0.08 wt.% carbon, a balanced amount of titanium, and unavoidable impurities. The above raw materials are subjected to multiple melting processes (e.g., by vacuum arc remelting) to form ingots. The specific steps are as follows:

[0056] The electrodes are pressed after mixing raw materials such as sponge titanium, aluminum granules, and aluminum alloys according to the design ratio.

[0057] The pressing electrode is subjected to vacuum consumable melting to form a titanium alloy ingot. The melting process can be repeated, for example, three times. The ingot size can be, for example, 120±3 mm in diameter for the first ingot, 170±3 mm in diameter for the second ingot, and 220±3 mm in diameter for the third ingot.

[0058] 2. Ingot processing and inspection

[0059] The surface of the titanium alloy ingot was treated to remove contamination and porosity defects. Then, samples were taken at approximately 50 mm from the riser and bottom of the ingot for chemical composition and gas analysis. The test results showed that all elements met the expected design requirements (as shown in Table 6).

[0060] 3. Forging process

[0061] The titanium alloy ingot undergoes multiple forging operations to ultimately form a titanium alloy forged slab. The forging process includes:

[0062] The first forging step involves opening the billet, heating it to a temperature of 1100±20℃, and performing a one-up and one-drawing process on the titanium alloy casting material. After forging, the material is air-cooled to room temperature and surface cracks are removed by grinding.

[0063] In the second forging step, the billet is reforged and heated to 950±10℃. The titanium alloy casting material is subjected to a one-up-one-drawing step. After forging, it is air-cooled to room temperature and the surface cracks are removed by grinding.

[0064] The third forging step involves re-forging the billet at a heating temperature of 990±10℃. The titanium alloy casting material undergoes a one-upsetting and one-drawing process, followed by air cooling to room temperature and grinding to remove surface cracks after forging.

[0065] The fourth forging step involves re-forging the billet at a heating temperature of 850±10℃, performing a one-up-one-drawing process on the titanium alloy casting material, and then returning it to the furnace after forging.

[0066] In the fifth forging step, the heating temperature is 820±40℃. The titanium alloy casting material is subjected to alternating unidirectional pressing and four-sided shaping operations to finally forge a titanium alloy forging slab blank with dimensions such as 400 mm x 300 mm x 60 mm.

[0067] 4. Sheet rolling

[0068] After the titanium alloy forged slab (e.g., heated in a high-temperature box-type resistance furnace) is subjected to a four-fire rolling operation, the specific steps of which are as follows:

[0069] The first rolling step is heated to 900 to 1100°C and the rolling rate is 30% to 50%, for example, from a thickness of δ60 mm to a thickness of δ30 mm ± 5 mm.

[0070] The second rolling step involves heating at 700 to 800°C and a rolling yield of 30% to 50%. For example, the thickness was reduced from δ30 mm to δ15 mm;

[0071] The third rolling step involves heating at 900 to 1100°C and holding the temperature for 20 to 60 minutes, followed by a water quenching step.

[0072] The fourth rolling step involves heating at 700 to 800°C, reversing the rolling direction, and rolling to 70% to 80% of the target plate thickness, for example, reducing the thickness from δ15 mm to δ4 ± 0.6 mm.

[0073] The finished titanium alloy sheet has high strength and ductility, making it suitable for applications requiring high strength and lightweight, such as golf club heads, aerospace, and the automotive industry.

[0074] Furthermore, the present invention also provides a titanium alloy material manufactured by the manufacturing method described above, wherein, based on a total weight of 100 wt.% of the titanium alloy material, the titanium alloy material comprises: 6.5 to 7.0 wt.% aluminum, 2.0 to 2.5 wt.% zirconium, 2.0 to 2.5 wt.% vanadium, 1.0 to 2.0 wt.% molybdenum, 0.5 to 1.5 wt.% iron, 0.1 to 0.3 wt.% boron, less than 0.15 wt.% silicon, 0 The titanium alloy contains less than 0.015 wt.% hydrogen, less than 0.15 wt.% oxygen, less than 0.05 wt.% nitrogen, less than 0.08 wt.% carbon, a balanced amount of titanium, and unavoidable impurities. The titanium alloy material has a tensile strength between 139 and 160 kSI, a yield strength between 139 and 150 kSI, an elongation between 12 and 16%, a hardness between 35 and 36 HRC, and a durability test firing test duration between 4000 and 6000 rounds. More preferably, the titanium alloy material has a tensile strength between 150 and 160 kSI, a yield strength between 142 and 145 kSI, an elongation between 12 and 13%, a hardness between 35 and 36 HRC, and a durability test firing test duration between 4000 and 6000 rounds.

[0075] Figures 2a to 2cThis diagram illustrates the metallographic structure obtained using a scanning electron microscope (SEM) according to an embodiment of the present invention. The titanium alloy produced by the titanium alloy material composition design and manufacturing method of the present invention exhibits a uniform and fine titanium alloy metallographic structure. Compared to Ti-6Al-4V, the present invention contains more strengthening elements such as Mo, Zr, and B, and achieves a more precise optimal ratio of individual components through composition design. This results in higher material strength. However, while increasing strength, elongation can easily decrease. The key to the present invention's ability to simultaneously achieve high elongation lies in the forging process. A single heat treatment process involves only one upsetting and drawing (upsetting + drawing), divided into multiple heat treatments to achieve a sufficient number of upsetting and drawing operations. The advantages are a finer grain size, reduced directionality, and fewer material defects. Multiple upsetting and drawing operations break down the strengthening elements formed by the precise optimal ratio of individual component design and distribute them evenly throughout the material, thereby enabling both higher strength and high elongation.

[0076] The titanium alloy material of this invention was not derived simply through limited experimental adjustments. Instead, this design involved countless experiments and meticulous data analysis, with the precise adjustment and testing of the proportions of each element. These processes are far beyond what traditional experiments can easily accomplish; rather, they represent a refined design guided by scientific theory and supported by extensive data. Such adjustments not only considered various theoretical deductions but also required repeated verification based on actual conditions to ensure the alloy's performance reached its optimal state. The success of this invention, achieved through countless experiments, is not accidental but a complete breakthrough in the foundations of existing technology.

[0077] While this invention optimizes existing technology, it does not simply involve selective material design; rather, it involves precise adjustments within the existing technological framework. Particularly in the proportions of elements such as aluminum, zirconium, and vanadium, this invention breaks through the limitations of traditional titanium alloy design, significantly improving the material's performance in terms of strength, toughness, ductility, high-temperature resistance, and machinability. This improvement is not a simple matter of arbitrarily selecting elements from existing alloys, but rather the result of numerous experimental adjustments, determining the most suitable proportions based on rigorous scientific data. Each adjustment is based on meticulous analysis, aiming to achieve an unexpected final effect, enabling the material to maintain superior mechanical properties even under extreme environments—something that existing technologies cannot achieve.

[0078] One of the core advantages of this invention is its unexpected technical effects. Although this invention is an extension of the applicant's previous Taiwan Application Publication No. 202100768A, the alloy composition design and element ratio of this invention achieve a significant breakthrough in performance. Through precise adjustments and corresponding process design and heat treatment conditions, the produced material exhibits stable high strength, high ductility, and durability over a long period under extreme conditions such as high impact and high temperature. Even during repeated processing and heat treatment, the alloy of this invention maintains its unchanged properties, giving it unexpected advantages in application that far exceed the capabilities of existing technologies. Therefore, this invention not only breaks through the limits of existing technologies but also ensures that it maintains excellent performance and long-term durability even after repeated use and processing.

[0079] Furthermore, the breakthrough in alloy design achieved in this invention was not achieved overnight. Its success stems from the precise control of the proportions of elements such as aluminum, zirconium, and vanadium. The addition and ratio of each component have been confirmed through countless experiments, a process that cannot be easily achieved using traditional experimental methods. It is important to emphasize that the unpredictable effects of this invention do not merely arise from the adjustment of a single element, but rather from the synergistic effect between elements, resulting in a holistic optimization of material properties. This process involves not only a large amount of experimental data and adjustments, but also a profound understanding and control of the material's inherent properties.

[0080] In summary, this invention presents a titanium alloy material with superior performance. Through a reasonable composition ratio and the synergistic effect of added elements, it achieves high strength, high ductility, and excellent corrosion resistance, demonstrating a competitive advantage in the market. Its high strength, excellent heat resistance, and outstanding ductility make it irreplaceable in high-strength, high-durability applications. Compared with existing technologies, the material of this invention exhibits greater stability in extreme environments, maintaining consistent performance over long periods, giving it significant market potential and a competitive edge in high-performance products such as golf clubs. Especially in applications with extremely high material performance requirements, the titanium alloy material of this invention demonstrates unexpected technical effects, proving its innovation and breakthrough within the existing technological framework.

Claims

1. A method for manufacturing a high-strength, impact-resistant titanium alloy material, characterized in that, The method includes the following steps: A titanium alloy casting material is provided, wherein, based on a total weight of 100 wt.% of the titanium alloy casting material, the titanium alloy casting material comprises: 6.5 to 7.0 wt.% aluminum, 2.0 to 2.5 wt.% zirconium, 2.0 to 2.5 wt.% vanadium, 1.0 to 2.0 wt.% molybdenum, 0.5 to 1.5 wt.% iron, 0.1 to 0.3 wt.% boron, less than 0.15 wt.% silicon, less than 0.015 wt.% hydrogen, less than 0.15 wt.% oxygen, less than 0.05 wt.% nitrogen, less than 0.08 wt.% carbon, a balance amount of titanium, and unavoidable impurities; The titanium alloy casting material is subjected to a forging step to form a titanium alloy forged slab, wherein the forging step includes: A first forging step, wherein the heating temperature of the first forging step is 1100±20℃; A second forging step, wherein the heating temperature of the second forging step is 950±10℃; A third forging step, wherein the heating temperature of the third forging step is 990±10℃; A fourth forging step, wherein the heating temperature of the fourth forging step is 850±10℃; A fifth forging step, wherein the heating temperature of the fifth forging step is 820±40℃; and The titanium alloy forged slab is subjected to a rolling step to form a titanium alloy forged sheet, wherein the rolling step includes: A first rolling step, wherein the heating temperature of the first rolling step is 900 to 1100°C; A second rolling step, wherein the heating temperature of the second rolling step is 700 to 800°C; A third rolling step, wherein the heating temperature of the third rolling step is 900 to 1100°C; A fourth rolling step, wherein the heating temperature of the fourth rolling step is 700 to 800°C.

2. The manufacturing method as described in claim 1, characterized in that, In the first forging step, the titanium alloy casting material is heated to 1100±20℃, and then the titanium alloy casting material is subjected to a one-upsetting and one-drawing step. After forging, it is air-cooled to room temperature and the surface cracks are removed by grinding.

3. The manufacturing method as described in claim 1, characterized in that, In the second forging step, the titanium alloy casting material is heated to 950±10℃, and then upsetting and drawing are performed on the titanium alloy casting material. After forging, it is air-cooled to room temperature and the surface cracks are removed by grinding.

4. The manufacturing method as described in claim 1, characterized in that, The third forging step involves heating the titanium alloy casting material to 990±10℃, then performing an upsetting and drawing process on the titanium alloy casting material, followed by air cooling to room temperature and grinding to remove surface cracks.

5. The manufacturing method as described in claim 1, characterized in that, The fourth forging step involves heating the titanium alloy casting material to 850±10℃, then performing an upsetting and drawing process on the titanium alloy casting material, and finally reheating it in the furnace after forging.

6. The manufacturing method as described in claim 1, characterized in that, In the fifth forging step, the titanium alloy casting material is heated to 820±40℃, and then the titanium alloy casting material is alternately subjected to unidirectional pressing and four-sided shaping operations to form the titanium alloy forging slab.

7. The manufacturing method as described in claim 1, characterized in that, The rolling rate of the first and second rolling steps is 30% to 50%.

8. The manufacturing method as described in claim 1, characterized in that, The third hot rolling step includes heating the titanium alloy forged slab to 900 to 1100°C and then hot rolling it, controlling the holding time to be 20 to 60 minutes, and then performing a water quenching step after the third hot rolling step.

9. The manufacturing method as described in claim 8, characterized in that, The fourth rolling step includes heating the titanium alloy forged slab after the water quenching step in the third rolling step to 700 to 800°C and performing reversing rolling, wherein the fourth rolling step is rolled to 70% to 80% of the target plate thickness.

10. A titanium alloy material manufactured by the manufacturing method according to any one of claims 1 to 9, characterized in that, Based on a total weight of 100 wt.% of the titanium alloy material, the titanium alloy material comprises: 6.5 to 7.0 wt.% aluminum, 2.0 to 2.5 wt.% zirconium, 2.0 to 2.5 wt.% vanadium, 1.0 to 2.0 wt.% molybdenum, 0.5 to 1.5 wt.% iron, 0.1 to 0.3 wt.% boron, less than 0.15 wt.% silicon, less than 0.015 wt.% hydrogen, less than 0.15 wt.% oxygen, less than 0.05 wt.% nitrogen, less than 0.08 wt.% carbon, a balance amount of titanium, and unavoidable impurities, wherein the titanium alloy material has a tensile strength between 139 and 160 kSI, a yield strength between 139 and 150 kSI, an elongation between 12 and 16%, a hardness between 35 and 36 HRC, and a durability test shelling test between 4000 and 6000 rounds.

Citation Information

Patent Citations

  • Tee diversion control valve

    CN202100768U